(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the status of knowledge and practice of respiratory disease prevention among workers in Phan Me, Thai Nguyen in 2024. Subject and method: Cross-sectional of 297 workers working at Phan Me coal mine, Thai Nguyen province. Results:. The proportion of workers with knowledge about respiratory disease prevention was 76.4%. Knowledge about environmental risk factors for respiratory diseases was correctly identified by 97.3% of the participants. A total of 69.7% of workers correctly recognized the symptoms of upper respiratory tract diseases. Workers who knew medical measures accounted for the highest proportion, 75.8%. 78.4% of workers wore masks throughout the work shift, 17.2% only wore masks when they saw dust, and 4.4% of workers did not use masks. The proportion of workers who were still smoking cigarettes/tobacco was 42.8%. 72.4% of workers had practices to prevent respiratory diseases at a satisfactory level and 27.6% did not meet the standards. Conclusion: There is a need for a plan to improve knowledge, especially knowledge of technical and technological measures, labor organization, knowledge of symptoms and treatment of respiratory diseases. Develop plans to improve smoking behavior and improve disease prevention behavior in the target group with good disease prevention effects to reduce the risk of disease.